Optimalisasi Pengembangan Multiple Intelligences Pada Anak Usia Dini di RA Alrosyid Kendal Dander Bojonegoro - Ulfa Ulfa (SELING: Jurnal Program Studi PGRA, 2017)
Early childhood is the golden age a period when children start to be sensitive and sensitive to receive various stimuli. At this time the child has a different power sensitive this research aims to optimize development of multiple intelligences of each individual child in RA Al-Rosyid Kendal Dander Bojonegoro. This research is a qualitative descriptive study; data collection techniques performed using the method of observation, interviews, and documentation. The results showed that development of multiple intelligences do whith storytelling, roleplaying, singing, and field trips that involve children directly. This way is very good for the development of the multiple intelligences early childhood and is very useful to their lives today, tomorrow and forever.